2016
DOI: 10.1016/j.bjane.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover trial comparing the Airtraq® NT, McGrath® MAC and Macintosh laryngoscopes for nasotracheal intubation of simulated easy and difficult airways in a manikin

Abstract: In a manikin, the Airtraq and the McGrath laryngoscopes appeared superior to the Macintosh laryngoscope when dealing with simulated airway scenarios. Both devices were associated with better views, intubation times and rates of success, especially in a simulated "difficult airway". Overall satisfaction was highest with the McGrath laryngoscope. Similar clinical studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…Rendeki et al [24] indicated that Airtraq was superior to the Macintosh laryngoscope in difficult airway intubation performed by novice users. This finding is in line with studies by other researchers [25,26].…”
Section: Discussionsupporting
confidence: 94%
“…Rendeki et al [24] indicated that Airtraq was superior to the Macintosh laryngoscope in difficult airway intubation performed by novice users. This finding is in line with studies by other researchers [25,26].…”
Section: Discussionsupporting
confidence: 94%
“…Gomez et al (19) reported that anesthesia residents needed the external laryngeal pressure maneuver in 32% of difficult nasotracheal intubation of a manikin with the Airtraq NT. In addition, they had to use Magill forceps, stylet, or operator change in some difficult cases.…”
Section: Discussionmentioning
confidence: 99%
“…0 = none of the glottis opening is seen, 100 = full visualization of larynx from the interarytenoid notch to anterior commissure of the vocal cords Visual analog scale (VAS) for field of view: 0–10-point scale. 0 = poor, 10 = excellent[ 2 13 ] Time to best view (TTBV): Time interval between blade entry past the lips and the laryngoscopist's verbal declaration that the best view for endotracheal intubation is achieved Tube at glottis (TAG): Time interval between blade entry past the lips and the tube passed the vocal cords Time to intubation (TTI): Time interval between blade entry past the lips and the appearance of first upstroke of the end-tidal CO 2 tracing Visual analog scale (VAS) for ease of use: 0–10-point scale. 0 = poor, 10 = excellent.…”
Section: Methodsmentioning
confidence: 99%